Normotensive rats with PCOS exhibit the hypertensive pattern: focus on oxidative stress. Issue 1 (9th December 2021) - Joksimovic Jovic, Jovana; Jovic, Nikola; Sretenovic, Jasmina; Zivkovic, Vladimir; Nikolic, Maja; Rudic, Jovan; Milošević, Verica; Ristić, Nataša; Andric, Kristina; Dimkic Tomic, Tijana; Milicic, Biljana; Jakovljevic, Vladimir
Abstract : Numerous evidence implies complex interrelations between polycystic ovary syndrome (PCOS) and hypertension (HT) in reproductive-age women. In this study, we aimed to investigate the potential strain differences in ovarian morphology, hemodynamic, and biochemical characteristics in an androgen-induced PCOS rat model. A total of 24 rats of 3 weeks old (12 Wistar Kyoto – WK and 12 spontaneously hypertensive rats – SHR) were divided into four groups: WK, WK PCOS, SHR, and SHR PCOS. PCOS was induced by daily s.c. injections of testosterone enanthate (1 mg/100 g body weight) administered for 5 weeks. PCOS induction led to estrus cyclicity cessation, cystic ovarian appearance, and sex hormones disturbances in both strains. The morphometric parameters in ovaries were altered in a manner of PCOS-related changes in both strains (higher number in preantral, atretic, and cystic follicles). Ultrasonographically, a significant decrease in ovarian volume (OV) was registered in PCOS groups but also in SHR compared to WK rats. All blood pressure parameters were higher in SHR compared to WK. PCOS modeling increased systolic, mean arterial, and pulse pressure in WK strain, while in SHR, only mean arterial and pulse pressure were higher. Alterations in oxidative stress parameters could provide a molecular basis for PCOS-related changes: in PCOS groups, thiobarbituric acid reactive substance and superoxide anion radical levels were higher in both strains, while superoxide dismutase and glutathione were significantly lowered.